2009
DOI: 10.1159/000202622
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracranial Hemorrhage in Children

Abstract: Aim: Spontaneous intracranial hemorrhage (SICH) in children is relatively less common as compared to adults, and there are limited studies addressing this issue in children. In this study, we analyze the etiology, clinical features, treatment options and outcome assessment in this population. Material and Methods: Fifty consecutive patients of spontaneous intracerebral bleed, aged 18 years and below, were retrospectively analyzed based on medical records and radiographic images. Status of the patient at the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 85 publications
2
27
1
2
Order By: Relevance
“…Most publications report a male preponderance [1,5,8], which is consistent with our findings (23/40 boys). Analyzing the mortality from childhood stroke in England and Wales over several decades, it was found that hemorrhage accounted for 71% of the deaths.…”
Section: Epidemiologysupporting
confidence: 93%
See 2 more Smart Citations
“…Most publications report a male preponderance [1,5,8], which is consistent with our findings (23/40 boys). Analyzing the mortality from childhood stroke in England and Wales over several decades, it was found that hemorrhage accounted for 71% of the deaths.…”
Section: Epidemiologysupporting
confidence: 93%
“…In our study, we found the incidence of symptomatic AVM in children to be 0.4/100,000, compared to the incidence of 0.7/100,000 estimated from previous publications [5]. In order to obtain the true incidence, it would be necessary to include not only children admitted with a definite diagnosis of AVM but also those with a postmortem diagnosis of AVM.…”
Section: Epidemiologycontrasting
confidence: 42%
See 1 more Smart Citation
“…Penelitian sebelumnya melaporkan bahwa adanya gangguan perdarahan akan sangat memengaruhi mortalitas, dengan angka kematian subyek dengan gangguan perdarahan hingga 41%. 10,12,13 Pemanjangan apTT menunjukkan derajat gangguan perdarahan dan kadar Hb dapat berhubungan dengan derajat dan lama perdarahan yang terjadi. Penurunan GCS dan refleks cahaya mungkin mencerminkan derajat proses desak ruang akibat peningkatan tekanan intrakranial.…”
Section: Pembahasanunclassified
“…Temuan ini berbeda dengan data terdahulu yang menunjukkan bahwa perdarahan lebih dari satu lokasi dan jenis perdarahan subdural memiliki prognosis lebih buruk. 13,14 Perbedaan tersebut kemungkinan dikarenakan penyebab perdarahan dan lebih banyaknya perdarahan subdural pada penelitian kami. Kami tidak memperhitungkan pengaruh jumlah perdarahan, jenis operasi, dan lama rawat yang RKP=rasio kemungkinan positif; RKN=rasio kemungkinan negatif; COP=cut off point merupakan keterbatasan penelitian ini karena faktor tersebut mungkin dapat berpengaruh.…”
Section: Pembahasanunclassified